2015
DOI: 10.3136/fstr.21.333
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Glycosides-rich Tea Cultivars (<i>Camellia sinensis</i> L.) in Japan

Abstract: In an effort to identify tea cultivars with high flavonol content, we measured flavonol glycoside levels in the tea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In the shoot and young leaf, the contents of flavonol glycosides, especially the quercetin glycosides, are obviously lower than those found in mature leaves. Kaempferol‐3‐ O ‐glucosyl‐(1‐3)‐rhamnosyl‐(1‐6)‐galactoside, quercetin‐3‐ O ‐glucosyl‐(1‐3)‐rhmnosyl‐(1‐6)‐glucoside and quercetin‐3‐ O ‐glucosyl‐(1‐3)‐rhamnosyl‐(1‐6)‐galactoside are the main flavonol glycosides of fresh leaves of C. sinensis (Monobe et al., ). Kaempferol, quercetin, and myricetin are the main flavonol aglycones of tea, in which the contents are similar between green and black teas after acid hydrolysis of tea infusion (Hertog, Hollman, & Van de Putte, ).…”
Section: Tea Chemistrymentioning
confidence: 99%
“…In the shoot and young leaf, the contents of flavonol glycosides, especially the quercetin glycosides, are obviously lower than those found in mature leaves. Kaempferol‐3‐ O ‐glucosyl‐(1‐3)‐rhamnosyl‐(1‐6)‐galactoside, quercetin‐3‐ O ‐glucosyl‐(1‐3)‐rhmnosyl‐(1‐6)‐glucoside and quercetin‐3‐ O ‐glucosyl‐(1‐3)‐rhamnosyl‐(1‐6)‐galactoside are the main flavonol glycosides of fresh leaves of C. sinensis (Monobe et al., ). Kaempferol, quercetin, and myricetin are the main flavonol aglycones of tea, in which the contents are similar between green and black teas after acid hydrolysis of tea infusion (Hertog, Hollman, & Van de Putte, ).…”
Section: Tea Chemistrymentioning
confidence: 99%
“…However, it would be too difficult to elucidate whether the functions of these subdominant ingredients are physiologically significant when we ingest green tea that has been brewed normally. We found previously that the presence of particular flavonoids in green tea depends on the cultivar (Camellia sinensis L.), and the contents of quercetin glycosides vary widely among different cultivars (13). Furthermore, we showed that a quercetin-rich cultivar, "Sofu," was more effective for suppressing the production of oxidized low-density lipoprotein (Ox-LDL) in hypercholesterolemic mice, compared with "Yabukita" which is a main tea cultivar in Japan (14).…”
mentioning
confidence: 74%
“…Flavonol glycoside levels in the diluted tea samples were measured by liquid chromatograph mass spectrometer (LC/MS). In accordance with our previous study (13), we determined the levels of two myricetin, five quercetin, and three kaempferol glycosides. With regard to anthocyanins, four delphinidin and four cyaniding glycosides were determined by high-performance liquid chromatography (HPLC), as described in our previous report (15).…”
Section: Green Tea Samplesmentioning
confidence: 99%
“…To date, dozens of literature reports described the use of various glycosides as aroma precursors, for example quercetin glycosides (Monobe et al ., ), 3‐methylbutanoyl glycosides (Iwasa et al ., ), phenolic glycosides (Yuan et al ., ) and β‐glucosidases (Sarry & GüNATA, ; Zhou et al ., ). But the thermal behaviour and the application of anisalcohol‐β‐galactoside was still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the costly and time-consuming nature of the natural extraction process for glycosides ( Sibul et al, 2016), and the chemical synthesis is selectivity limited and environmental unfriendly (Schwab et al, 2015;Yang & Yu, 2017), enzymatic approach was established by employing the recombinant b-galactosidase with transgalactosylation activity to synthesize anisalcohol-b-galactoside. The synthetic product was characterized by mass spectroscopy (MS) and proton nuclear magnetic resonance spectroscopy ( 1 H NMR, To date, dozens of literature reports described the use of various glycosides as aroma precursors, for example quercetin glycosides (Monobe et al, 2015), 3-methylbutanoyl glycosides (Iwasa et al, 2015), phenolic glycosides (Yuan et al, 2018) and b-glucosidases (Sarry & G€ uNATA, 2004;Zhou et al, 2017). But the thermal behaviour and the application of anisalcohol-b-galactoside was still rarely reported.…”
Section: Introductionmentioning
confidence: 99%